1989
DOI: 10.1210/endo-125-2-1060
|View full text |Cite
|
Sign up to set email alerts
|

Mullerian Inhibiting Substance in the Adult Rat Ovary During Various Stages of the Estrous Cycle*

Abstract: Mullerian inhibiting substance (MIS) in the adult rat ovary can be detected by immunohistochemistry in the granulosa cells of growing preantral follicles and in the cumulus oophorus and periluminal granulosa cells of antral follicles in estrus, metestrus, diestrus, and proestrus. Neither the corpus luteum nor atreitic follicles stained for MIS. During proestrus, dramatic changes occurred in the large preovulatory antral follicles, which early in the day manifest intense MIS-specific staining in the granulosa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 53 publications
6
53
0
4
Order By: Relevance
“…Similar patterns occur in non-human primates (Modi et al 2006), mice (Gruijters et al 2003), rats (Ueno et al 1989, Hirobe et al 1994, Baarends et al 1995, Siberian hamsters (Shahed & Young 2013), cows (Monniaux et al 2012), goats (Monniaux et al 2012, Rocha et al 2016, sheep (Bezard et al 1987) and brushtail possums (Juengel et al 2002). AMH expression declines as follicles progress through the large antral stage of folliculogenesis, with little AMH being produced in preovulatory follicles (Ueno et al 1989, Weenen et al 2004, Jeppesen et al 2013. However, AMH expression remains elevated in the cumulus granulosa cells of large follicles until immediately prior to ovulation (Ueno et al 1989, Hirobe et al 1994, Monniaux et al 2012, Merhi et al 2013.…”
Section: Anti-müllerian Hormone Expression In the Ovarymentioning
confidence: 78%
See 1 more Smart Citation
“…Similar patterns occur in non-human primates (Modi et al 2006), mice (Gruijters et al 2003), rats (Ueno et al 1989, Hirobe et al 1994, Baarends et al 1995, Siberian hamsters (Shahed & Young 2013), cows (Monniaux et al 2012), goats (Monniaux et al 2012, Rocha et al 2016, sheep (Bezard et al 1987) and brushtail possums (Juengel et al 2002). AMH expression declines as follicles progress through the large antral stage of folliculogenesis, with little AMH being produced in preovulatory follicles (Ueno et al 1989, Weenen et al 2004, Jeppesen et al 2013. However, AMH expression remains elevated in the cumulus granulosa cells of large follicles until immediately prior to ovulation (Ueno et al 1989, Hirobe et al 1994, Monniaux et al 2012, Merhi et al 2013.…”
Section: Anti-müllerian Hormone Expression In the Ovarymentioning
confidence: 78%
“…AMH expression declines as follicles progress through the large antral stage of folliculogenesis, with little AMH being produced in preovulatory follicles (Ueno et al 1989, Weenen et al 2004, Jeppesen et al 2013. However, AMH expression remains elevated in the cumulus granulosa cells of large follicles until immediately prior to ovulation (Ueno et al 1989, Hirobe et al 1994, Monniaux et al 2012, Merhi et al 2013. AMH expression is negligible in atretic follicles (Weenen et al 2004).…”
Section: Anti-müllerian Hormone Expression In the Ovarymentioning
confidence: 99%
“…1B). At 48 h after treatment, granulosa cells of growing follicles in the treatment group showed increased staining of anti-Mullerian hormone (AMH), a marker for secondary/preantral follicles (11) (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…4c,d). This is of note because MIS expression by granulosa cells of the cycling rat ovary is greatest in preantral and antral follicles prior to ovulation, particularly in the cell layers closest to the oocyte (Ueno et al, 1989), and because MIS has been shown to inhibit oocyte meiosis in vitro (Takahashi et al, 1986). Again, such signal localization is suggestive that R1 is a candidate MIS receptor.…”
Section: Developmental Expression Of Rl-r4 Mrnamentioning
confidence: 92%